2015
DOI: 10.1038/leu.2015.174
|View full text |Cite
|
Sign up to set email alerts
|

The BAFF receptor TACI controls IL-10 production by regulatory B cells and CLL B cells

Abstract: Interleukin (IL)-10-producing B cells (B10 cells) have emerged as important regulatory players with immunosuppressive roles. Chronic lymphocytic leukemia (CLL) B cells also secrete IL-10 and share features of B10 cells, suggesting a possible contribution of CLL B cells to immunosuppression in CLL patients. Factors controlling the emergence of B10 cells are not known. B cell-activating factor of the tumour necrosis factor (TNF) family (BAFF) is critical for B cell maturation and survival, and is implicated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 57 publications
(85 reference statements)
3
69
1
Order By: Relevance
“…Moreover, we found an increase of CD73 in B10 cells in BAFFtg mice especially when they were tolerised with MTX. Interestingly, it has been previously shown that BAFF stimulation of B cells increased IL-10 production in the supernatant22 and that B cells from BAFFtg mice could secrete more IL-10 23. Since B10 cells require in vitro activation to be studied, we sought to also explore Breg precursors as described previously 19…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found an increase of CD73 in B10 cells in BAFFtg mice especially when they were tolerised with MTX. Interestingly, it has been previously shown that BAFF stimulation of B cells increased IL-10 production in the supernatant22 and that B cells from BAFFtg mice could secrete more IL-10 23. Since B10 cells require in vitro activation to be studied, we sought to also explore Breg precursors as described previously 19…”
Section: Discussionmentioning
confidence: 99%
“…Upon CSF-1R neutralization, NLC were virtually undetectable in these cultures (Figure 1C, D, E). In contrast, neutralization of the cytokines IL-10 and IL-6, which have been previously implicated in CLL and/or NLC biology (15, 2730), did not significantly inhibit NLC generation. CSF-1 was at or below the limit of detection (by ELISA) in culture supernatants obtained from NLC cultures (data not shown).…”
Section: Resultsmentioning
confidence: 61%
“…40,43 Consistently, hypoxia protected CLL cells from drug-induced apoptosis and triggered production of IL-10, which is considered the hallmark cytokine for regulatory B cells. 57 Monocytes in hypoxic conditions differentiated more readily into M2 macrophages, becoming more efficient supporters of CLL survival, while T lymphocytes showed impaired proliferation and increased expression of Treg markers. The effects converged to create ideal conditions for tumor growth in closed environments.…”
Section: Discussionmentioning
confidence: 99%